He Dynamics of Relation between the State and Local Religions in Indonesia: Between Idealism and Reality - Adib ‘Aunillah Fasya; Alif Al Hilal Ahmad; Muhammad Lukman Arifianto; Zainurrakhmah Zainurrakhmah (Al-Albab, 2015)
This paper, in general, discusses the relation between the state and local religions in Indonesia. There is no doubt that Indonesia is one of the countries which has local religions or beliefs with a considerable number of followers, so that the state needs to protect of the followers of these religions. However, after the passing of the government regulation on the recognition of particular official religions in the country, various issues related to formally unrecognized religions began to emerge, including discrimination by the government, especially in administrative matters, as well as social discrimination by the community that denies their existence. Various methods are used by the state to minimize the discriminatory attitudes by issuing multiple regulations and policies, but still it is not considered satisfactory to satisfy all parties, especially those who have been discriminated.